Factors of urban poverty in Sungai Petani / Muhammad Khaleq Murdipi and Tuan Muhamad Khalif Tuan Mohd Zulkifly - Murdipi, Muhammad Khaleq; Tuan Mohd Zulkifly, Tuan Muhamad Khalif (2019)
Nair (2009) has stated that the studies on poverty has being too focused on the rural area only while too little studies has being conducted to understand more about the urban poverty phenomenon. Statistics showed that the actual number of urban poor and slum dwelers in cities is still significantly high where in 2009, a total of 69,900 households were reported as being urban poor (KPWKM, 2011). Sabstu (2014) has mentioned that the income is spent on the basic necessities and others while the majority revenue is used for instalment payments. After paying those instalments, the household will not have any surplus left from their monthly income to spend on other aspects of life or for the saving purposes. Hence, there are issues on how these urban poor consumer to cope with the higher cost of living which individuals with low-income especially are associated with low well-being (Oshio & Urakawa, 2013). Some scholars sees the issue of urban poverty as an economic phenomenon resulted from the excessive and rapid urbanisation in a country (Abd Aziz et al., 2010). In other words, rapid pace of urbanization causes vulnerability among the urban dwellers therefore caused urban poverty to happen (Siwar, Ferdoushi, Bashawir & Md. Shahin, 2016). In addition of lack of education received by urban poor, there are also another issues that being added such as lack of training skills, productive knowledge and transforms human beings into more valuable human capital education (Mauro, 1998).